2013
DOI: 10.1371/journal.pone.0053659
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia valaisiana Resist Complement-Mediated Killing Independently of the Recruitment of Immune Regulators and Inactivation of Complement Components

Abstract: Spirochetes belonging to the Borrelia (B.) burgdorferi sensu lato complex differ in their resistance to complement-mediated killing, particularly in regard to human serum. In the present study, we elucidate the serum and complement susceptibility of B. valaisiana, a genospecies with the potential to cause Lyme disease in Europe as well as in Asia. Among the investigated isolates, growth of ZWU3 Ny3 was not affected while growth of VS116 and Bv9 was strongly inhibited in the presence of 50% human serum. Analyzi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 68 publications
4
13
0
Order By: Relevance
“…One main finding regarding complement activation was the significant difference in found between the two strains of Borrelia . In accordance with previous findings [32] , we found that the complement-sensitive strain B. garinii LU59 induced a higher level of complement activation, as measured by the generation of C3a and sC5b-9 in plasma and detected by ELISA. Complement activation induced by the presence of Borrelia -specific antibodies resulted in a significant increase in generated sC5b-9, in agreement with other studies of the deposition of C5b-9 on the bacterial surface [8] , [18] , [33] , [34] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…One main finding regarding complement activation was the significant difference in found between the two strains of Borrelia . In accordance with previous findings [32] , we found that the complement-sensitive strain B. garinii LU59 induced a higher level of complement activation, as measured by the generation of C3a and sC5b-9 in plasma and detected by ELISA. Complement activation induced by the presence of Borrelia -specific antibodies resulted in a significant increase in generated sC5b-9, in agreement with other studies of the deposition of C5b-9 on the bacterial surface [8] , [18] , [33] , [34] .…”
Section: Discussionsupporting
confidence: 93%
“…In addition, low amounts of C4BP were detected on both strains, with a non-significantly higher level on B. garinii LU59. Binding of C4BP to B. garinii in the literature is contradictory, studies in which no binding of C4BP was detected when a similar experimental setup has been reported [13] , [32] as well as studies in line with data presented here where binding of C4BP is observed [15] .…”
Section: Discussionsupporting
confidence: 63%
“…Investigating degradation of different complement components (C1q, C3, C3b, C4, C5, C6, C7, C8 and C9), none of these molecules were enzymatically cleaved by spirochetes (Fig. F) concurrently confirming our previous observations obtained with B. burgdorferi , B. garinii and B. valaisiana , which also lacked any proteolytic activity for complement C3, C3b, C4, C4b and C5 (Schwab et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, the Lyme disease spirochete B . valaisiana strain ZWU3 Ny3 was shown to possess a novel mechanism of complement inhibition independent of host complement regulator recruitment/mimicry [ 79 ]. Although a molecular mechanism has not been elucidated, the authors hypothesize that the inhibitory mechanism present in this strain of B .…”
Section: Discussionmentioning
confidence: 99%